Legal Implications of De Facto States on Diplomatic Trade and Industrial Protection - Saurav Kumar (The International Journal of Law Review and State Administration, 2026)
This study aims to analyze in depth the legal implications of the existence of a de facto state on the certainty of the international trade regime, the enforceability of bilateral/multilateral trade agreements, and the protection schemes for intellectual property rights (IPR) and industrial assets. Using normative legal research methods and a doctrinal approach, this study examines the interaction between the doctrine of non-recognition and pragmatic needs in cross-border business transactions. The results show that the lack of de jure status often limits the access of de facto states to international financial institutions (such as the WTO and WIPO), hinders the enforcement of trade contracts, and weakens the legal protection of intellectual property and industrial investments from expropriation or counterfeiting. Nevertheless, modern international legal practice shows the emergence of the doctrine of necessity and informal commercial mechanisms to minimize the legal vacuum. This study concludes the need to formulate an adaptive transnational legal framework to protect the rights and interests of commercial entities without sacrificing the political sovereignty of the parent state.